Arthropod immunity : characterisation of the humoral immune responses in two species of arthropods - the Kalahari millipede triaenostreptus triodus (attems) and the scorpion opisthopthalmus latimanus (Koch). - Van der Walt, Etienne (My University, 1998)
This is the first report comparing the inducible humoral immune responses of' two long-lived arthropods. Inducible humoral immune responses were detected in two arthropods namely, the scorpion Opisthopthalmus latitnanus (Arachnida) and the millipede Triaetiostreptus triodus (Diploooda: Spirostreptidae). These anti-bacterial activities were elicited by "ve gram-negative and gram-positive bacteria. A dramatic hemocytopenia was demonstrated in both the millipede and scorpion after experimental infection, suggesting the possible release of a hemocyte depletion factor. The anti-bacterial humoral responses of the millipede and the scorpion were similar in magnitude to those that have been reported for a large variety of short-lived insects. I also provide further characterisation of the anti-bacterial defence proteirus) of the Kalana n millipede. My results suggest that the humoral immune response of arthopods may have a long and conserved phylogeny.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science.
Keywords: Arthropoda.; Immune response.; Scorpions.; Millipedes.